2009
DOI: 10.1073/pnas.0908200106
|View full text |Cite
|
Sign up to set email alerts
|

Melanin-concentrating hormone directly inhibits GnRH neurons and blocks kisspeptin activation, linking energy balance to reproduction

Abstract: A link between energy balance and reproduction is critical for the survival of all species. Energy-consuming reproductive processes need to be aborted in the face of a negative energy balance, yet knowledge of the pathways mediating this link remains limited. Fasting and food restriction that inhibit fertility also upregulate the hypothalamic melanin-concentrating hormone (MCH) system that promotes feeding and decreases energy expenditure; MCH knockout mice are lean and have a higher metabolism but remain fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 69 publications
3
82
0
4
Order By: Relevance
“…MCH activates inhibitory G i -coupled MCHR1 receptors , reduces presynaptic activity (Gao, 2009), and suppresses neuronal firing (Wu et al, 2009;Sears et al, 2010). Stimulating MCH projections in the LS reduced action potential firing, but this does not reflect an inhibitory action of MCH but rather a glutamate-dependent GABA release.…”
Section: Gabamentioning
confidence: 99%
“…MCH activates inhibitory G i -coupled MCHR1 receptors , reduces presynaptic activity (Gao, 2009), and suppresses neuronal firing (Wu et al, 2009;Sears et al, 2010). Stimulating MCH projections in the LS reduced action potential firing, but this does not reflect an inhibitory action of MCH but rather a glutamate-dependent GABA release.…”
Section: Gabamentioning
confidence: 99%
“…Anatomically, this is plausible since various studies in female rodents have reported the close apposition of MCH fibres to hypothalamic GNRH neurones (Smith & Grove 2002, Williamson-Hughes et al 2005, Wu et al 2009, and Mchr1 mRNA has been detected in GNRH neurones (Williamson-Hughes et al 2005). Approximately 85-90% of GNRH neurones were reportedly in contact with MCH-immunopositive projections (Williamson-Hughes et al 2005).…”
Section: Part 2: Mch and Reproductive Functionmentioning
confidence: 97%
“…Specifically, there was a significant increase in MCH innervation of the ventrolateral subdivision of the ventromedial nucleus of the hypothalamus and the ventral premammillary nucleus, leading the authors to propose that MCH may be acting to inhibit reproductive function and behaviours during lactation via this pathway. A further finding that the MCH neurones of the mPOA co-express the inhibitory GABA-synthesising enzyme glutamic acid decarboxylase provoked the hypothesis that the MCH/GABA neurones may inhibit pulsatile LH secretion during lactation (Rondini et al 2010) via the close apposition of MCH and NEI terminals to GNRH cell bodies (Smith & Grove 2002, Williamson-Hughes et al 2005, Ward et al 2009, Wu et al 2009 or via MCHR1, which is co-expressed in a subpopulation of GNRH neurones (Williamson-Hughes et al 2005). Finally, since the mPOA MCH neurones of female rats were in close apposition to terminals immunoreactive for AgRP, a-melanocyte-stimulating hormone and CART, neurobiological regulators clearly implicated in energy balance (Rondini et al 2010), it could be that the mPOA is one site where MCH is active in the integration of ingestive and reproductive behaviours, at least in conditions of negative energy balance that are customary during lactation.…”
Section: Part 3: Mch Energy Balance and Fertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…administration of an a-MSH-like agonist to ewes increases KISS1 mRNA in the POA and results in a rise in plasma LH (Backholer et al 2009). Conversely, the orexigenic peptide melanin-concentrating hormone, which is highly expressed in the lateral hypothalamus, inhibits the stimulatory effects of kisspeptin on GnRH neurons (Wu et al 2009). …”
Section: Kisspeptin Provides a Link Between Nutritional Status And Fementioning
confidence: 99%